Effect of Explosive Leg Power, Balance and Flexibility of The Wrist on Lay Up Shoot Ability in Basketball Athletes - Andi Mas Jaya; Andi Febi Irawati; Maria Herlinda Dos Santos (Universitas PGRI Palembang, 2023)
This research is a type of Ex Post Facto research that uses a path analysis research design. The population is all basketball athletes PERBASI Kab. Sinjai with a total sample of 30 female athletes. The sampling technique is a saturated sample or the total population. The data analysis technique used was descriptive analysis, requirements test, path analysis through the SPSS 20.00 program at a significant level of 95% or α 0.05. The research results show that; (1) There is a direct effect of leg explosive power on wrist flexibility in basketball athletes in PERBASI Kab. Sinjai with a beta value of 0.603 with a significant level of 0.000 <α0.05; (2) There is a direct effect of balance on wrist flexibility in PERBASI athletes in Kab. Sinjai with a beta value of 0.378 with a significant level of 0.019 <α0.05; (3) There is a direct effect of leg explosive power on the ability to lay up shoot in basketball athletes from PERBASI Kab. Sinjai with a beta value of 0.380 with a significant level of 0.002 <α0.05 (4) There is a direct effect of balance on lay-up shoot ability in PERBASI Kab. Sinjai with a beta value of 0.289 with a significant level of 0.005 <α0.05; (5) There is a direct effect of wrist flexibility on the ability to lay up shoot in basketball athletes from PERBASI Kab. Sinjai with a beta value of 0.337 with a significant level of 0.004 <α0.05; (6) There is no effect of leg explosive power through wrist flexibility on the lay up shoot ability of PERBASI Kab. Sinjai with a beta value of 0.203 (0.203 <0.380); (7) There is no effect of balance through wrist flexibility on the lay up shoot ability of PERBASI Kab. Sinjai with a beta value of 0.127 (0.127 <0.28 9).